Effective Percutaneous Repositioning of an Active Fixation ICD Lead - Maria Grazia Bongiorni; Giovanni Coluccia; Luca Segreti; Luca Paperini; Ezio Soldati (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2015)
We report a case of effective trans catheter repositioning of an ICD lead that was displaced during a trans venous extraction procedure of another malfunctioning ICD lead. This original technique was effective also in screwing-in the active fixation tip of the lead. Skilled operators could take into account this technique to avoid the re-opening of the device pocket, when dealing with specific situations at high risk of infection.